A note on an extension of Lindelöf's theorem to meromorphic functions - Mohammad Salmassi (International Journal of Mathematics and Mathematical Sciences)
S. M. Shah [3] has given an extension of Lindelöf's Theorem to meromorphic functions. He also obtained an expression for the characteristic function of a meromorphic function of integer order. In this note we give estimates for log|f(reiθ)| of such functions.